Evaluating Multi-Party Verification for Land Certificates Using Hyperledger Fabric - Rizqulloh Brilliant 'Ainur Rofiq Rofiq; Joko Sutopo (bit-Tech, 2025)
Blockchain technology provides a secure and transparent framework for managing land ownership records. However, most existing systems lack mechanisms that allow multiple authorities to verify transactions collaboratively before they are finalized. This study evaluates the implementation of a multi-party verification model for land certificate transactions using Hyperledger Fabric, a permissioned blockchain platform that supports configurable endorsement policies to simulate multi-signature behavior. The system architecture involves three endorsing organizations: BPN (National Land Agency), PPAT (Land Deed Officials), and the Local Government, each acting as an independent validator within the blockchain network. A series of performance tests were conducted to measure transaction latency, endorsement success rate, and throughput under single-, two-, and three-party endorsement configurations. Results show that the average latency increased from 1.13 seconds under a single-party policy to 2.43 seconds under a three-party policy, while throughput declined from 63.4 to 37.2 transactions per second. Despite this reduction, the system maintained a 100 percent endorsement success rate across all configurations, indicating consistent policy enforcement by Hyperledger Fabric’s validation system chaincode. The findings highlight the potential of Hyperledger Fabric as a foundation for transparent and auditable land registration. This approach directly supports Indonesia’s digital governance framework by providing a technical model for secure inter-agency coordination, which is critical for the national transition to electronic land certification and enhancing institutional accountability. Key limitations of this study, representing directions for future work, include the controlled simulation environment and the need for integration with Indonesia’s national Public Key Infrastructure (PKI) to ensure full legal compliance.